Estratégias analíticas para a avaliação química de solos e liquens da Antártica marítima - Guerra, Marcelo Braga Bueno (Universidade Federal de São Carlos, 2011)
The aim of this PhD thesis is the ample study of soil and lichen samples from Antarctica, collected in regions under strong anthropogenic impact. Surface soil samples were collected around several scientific stations: Brazilian (Comandante Ferraz), Argentinian (Esperanza), Chilean (Frei Montalva and Escudero), Chinese (Great Wall), Russian (Bellingshausen) and Uruguaian (Artigas). Control soil samples were also collected, for representing areas with low anthropic influence (far away from the local stations). Lichen samples (Usnea antarctica and Usnea aurantiacoatra) were collected near the Chilean and Russian stations, as well as in a control point far 0.5 km from the nearest station. X-ray Fluorescence was used as an analytical tool for the preliminary evaluation on metal contamination in the soil samples. Several extraction solutions (aqua regia, sequential extraction procedure, DTPA and CaCl2 solutions) were used to assess the amounts of metals in the soil samples. For Cd, Cr, Cu, Mn, Ni, Pb and Zn determination in the soil extracts, some analytical strategies were employed, such as fast sequential determination by FAAS in the conventional mode, as well as by using STAT-FAAS and TS-FF-AAS for evaluating Cd and Pb determination in DTPA soil extracts. The chemometric tools: HCA, PCA and PARAFAC were used for soil data treatment. Enrichment factors were calculated in order to infer about the degree of soil contamination. Soil samples collected around the stations diesel tanks were enriched with Cr and Pb. Soil samples from Esperanza station are the most contaminated ones, reaching 46, 18993 and 4823 mg kg-1 for Cd, Pb and Zn, respectively, for the strongest contaminated sites. The use of Flame-AAS and STAT-FAAS in the fast sequential mode appears as a good way that combines higher analytical throughput and better sensitivity (STAT-FAAS). Besides that, minimization of toxic wastes generation and xv economy of reagents are analytical advantages of this approach. The employment of chemometric tools are also an important strategy allowing the visualization of sample groupings and the variables related to them. A fast and simple method for pseudototal determination of metals in soil samples was developed. In this method, the samples were extracted with lower amount of aqua regia and in a reduced time (when compared with the official method) by using inexpensive centrifuge tubes. LAICP- MS was evaluated for direct determination of lead in the lichen samples and to access the distribution profile of this element in the organism structures. Lichen samples from heavily anthropogenic sites (near the stations) have the highest Pb concentrations ([Pb] = 8.71 mg kg-1 for the most contaminated sample and [Pb] = 1.12 mg kg-1 for the control point). LA-ICP-MS emerges as an adequate analytical method for direct Pb determination in lichen samples, notably when using carbon (naturally present in the samples) as internal standard. The medulla region of the lichen thalli is the main Pb bioacumulating lichen region.
Analytical strategies for the chemical analysis of soils and lichens from Maritime Antarctica
Keywords: Química analítica; Antártica; Solos; Metais; Espectrometria; Quimiometria; CIENCIAS EXATAS E DA TERRA::QUIMICA